2021
DOI: 10.1016/j.ssmph.2021.100915
|View full text |Cite
|
Sign up to set email alerts
|

The impact of income definitions on mortality inequalities

Abstract: Income is a strong predictor of adult mortality. Measuring income is not as simple as it may sound. It can be conceptualized at the individual or the household level, with the former better reflecting an individual's earning ability, and the latter better capturing living standards. Furthermore, respondents are often grouped into income categories based on their positions in the income distribution, and this operationalization can be done on the basis of age-specific or total population income distributions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Likewise, differences in the used socioeconomic variables, for example household vs. individual income, may lead to varying results in health inequality research. 26 However, in our study, income and educational levels both had a similar association on the adherence estimates.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Likewise, differences in the used socioeconomic variables, for example household vs. individual income, may lead to varying results in health inequality research. 26 However, in our study, income and educational levels both had a similar association on the adherence estimates.…”
Section: Discussionsupporting
confidence: 50%
“…The annual income was capped to a maximum of 100 000 euros to avoid patients’ identifiability due to high incomes. To account for changes in income over time and age, patients were divided into age group and AF diagnosis year specific income quartiles, i.e., each 10‐year age group during each cohort entry year was divided into income quartiles using age group and entry year specific cut‐points 26 . Divisions to income quartiles were performed separately in the implementation and persistence study cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Shi et al. could show that the level of income inequalities in life expectancy is to some extent also influenced by the definition of income ( 55 ). In accordance with this, previous analyses have shown that while the total level of income inequality tends to vary, both household income and individual income are largely reliable to measure health inequalities ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid patients’ identifiability due to high incomes, the annual income was capped to a maximum of 100 000 euros. Since income level is associated with age and the mean income level of patients may vary according to the cohort entry year, the patients were divided into age group and AF diagnosis year specific income quintiles, i.e., each 10-year age group during each cohort entry year was divided into income quintiles using age group and entry year specific cut-points [23] . Since different definitions of income levels may significantly affect the results, sensitivity analysis was performed by using cohort level income quintile cut-points [23] .…”
Section: Methodsmentioning
confidence: 99%